Penerapan Ice Breaking dalam Layanan Bimbingan Klasikal untuk Menstimulasi Konsentrasi Belajar Siswa - Nakhma’ussolikhah; Nurul Ainadhynanty; Dian Widiantari; Ficky Adi Kurniawan (Journal Of Education Research and Inovative, 2026)
This study aims to describe the implementation of ice breaking in classical guidance services and analyze students’ responses to the use of ice breaking as a strategy to stimulate the learning concentration of eleventh-grade students at MAN 1 Cirebon. This research employed a qualitative approach with a case study design. Data were collected through observation, interviews, and documentation. The research informants consisted of one Guidance and Counseling teacher and seven eleventh-grade students, while classroom observation was conducted in one class consisting of 35 students. The data were analyzed thematically through data reduction, coding, theme grouping, and narrative presentation. The results show that ice breaking was implemented flexibly at the beginning, middle, or end of the service according to students’ conditions. The Guidance and Counseling teacher used ice breaking when students began to feel bored, sleepy, less responsive, or unfocused. Students’ responses indicate that ice breaking created a more relaxed, enjoyable, and less tense classroom atmosphere. Students also felt fresher, more enthusiastic, and more prepared to participate in the service. However, the benefits of ice breaking depended on activity variation, teacher facilitation, and its relevance to the service material. The findings imply the need for varied, contextual, and meaningful activities overall.